NETWORKED PROFESSIONAL LEARNING: THE INFLUENCE ON UNIVERSITY TEACHERS’ SELF-EFFICACY TO CREATE A POSITIVE UNIVERSITY CLIMATE - Malykhin, Oleksandr; Aristova, Nataliia; Dyka, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of this study is to evaluate the influence of networked professional learning on university teachers’ self-efficacy to create a positive university climate. The study also provides, on the one hand, the theoretical overview of the scientific papers by Ukrainian and foreign scholars related to clarifying the understanding of the research leading concepts of “networked professional learning” and “informal learning” in scientific literature and, on the other hand, empirical research into the influence of networked professional learning on university teachers’ self-efficacy to create a positive university climate. The experimental research was conducted in two stages. During the first stage of research a total of 267 university teachers who volunteered to participate in the research were interviewed for eliciting information concerning their participation activity rate in specially focused network pedagogical communities. During the second stage 108 university teachers selected from the total population by homogeneous sampling completed a questionnaire on teacher self-efficacy developed by A. Bandura. Although the findings of the study show that not all university teachers believe that there is a clear link between networked professional learning and high level of university teachers’ self-efficacy, the majority of respondents recognize the increasing influence of informal learning in general and networked professional learning in particular on their professional growth. For understanding the research leading concepts and interpreting obtained findings methods of scientific literature analysis and mathematical statistics were used.